Electrochemical study of anti-platelets tirofiban HCl in dosage form using nanomaterials modified sensors: developed and green assessed by eco-scale and complex-GAPI approach - Mohamed. Rizk; Maha Mahmoud Abou El-Alamin; Ola Abd Elkhalek; Hassan A. M. Hendawy (BMC Chemistry)
Abstract Tirofiban hydrochloride is used to inhibit platelet aggregation, which has a significant impact on the treatment of congestive heart failure the most common cause of death according to WHO. Therefore, its quantification in pharmaceutical dosage form is critical. In this work, an electrochemical method for the determination of tirofiban HCl in pharmaceutical dosage form was developed and validated. Carbon paste electrode modified with multi-walled carbon nanotubes (MWCNT) was utilized to examine the electrochemical response of tirofiban hydrochloride. Scanning electron microscopy and Energy-dispersive X-ray analysis was used to investigate the morphology of this electrode. A linear response was obtained within the range of (27.00–745.00 ng/mL) (5.4 × 10–5 M–1.5 × 10−3 M) with a correlation coefficient of 0.9995, and a detection limit of 15.50 ng/mL (3.1 × 10–5 M). The greenness profile of the method was assessed utilizing the eco-scale and the green analytical procedure Index.